2013
DOI: 10.1007/s10530-013-0419-x
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic increase in the Zembretta Yelkouan shearwater breeding population following ship rat eradication spurs interest in managing a 1500-year old invasion

Abstract: The ship rat (Rattus rattus) was introduced 1,500 years ago to the Zembra Archipelago (Tunisia) and was eradicated in October-November 2009 on two of its islands, Zembretta and Zembrettina. This eradication was performed 2 years after the discovery of a small colony of Yelkouan shearwaters (Puffinus yelkouan), a species recently up-listed to the vulnerable IUCN extinction risk category. For 2 years before and 3 years after rat eradication, the Zembretta Yelkouan shearwater breeding colony was checked yearly at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…Increases in the size of nesting population have also been recorded after eradication (e.g. Bourgeois et al 2013). On Greek islands, an increase of the reproductive success of the endangered Eleonora's falcon Falco eleonorae following rat removal was reported (Hellenic Ornithological Society 2006).…”
Section: Impacts Of Invasive Species and Benefits Of Their Removal Fomentioning
confidence: 99%
“…Increases in the size of nesting population have also been recorded after eradication (e.g. Bourgeois et al 2013). On Greek islands, an increase of the reproductive success of the endangered Eleonora's falcon Falco eleonorae following rat removal was reported (Hellenic Ornithological Society 2006).…”
Section: Impacts Of Invasive Species and Benefits Of Their Removal Fomentioning
confidence: 99%
“…In fact, the dramatic increase in some shearwaters' breeding population immediately following rat eradication (Bourgeois et al 2013;Marie et al 2014;VanderWerf et al 2014) suggested that procellariid seabirds may select their breeding sites according to direct cues. However, we hypothesized that this selection could also be at least partially driven by olfaction (avoidance of burrows 'smelling' of rats), with a predation risk assessment based upon predator chemical cues.…”
Section: Discussionmentioning
confidence: 99%
“…Procellariid seabirds may also have locally developed indirect, cryptic anti-predator behaviours so as to reduce the impact of rats (e.g. Ruffino et al 2009;Bourgeois et al 2013). Interestingly, the extent and the rapidity of some seabird population recovery after rat eradication (Bourgeois et al 2013) suggest that rats had previously prevented birds from breeding, and points to an as yet unidentified behavioural process enabling shearwaters to detect and avoid rat-infested islands, and to rapidly (re)colonize islands when rats are removed.…”
Section: Introductionmentioning
confidence: 99%
“…Invasive rats (Rattus exulans, R. norvegicus & R. rattus) have been introduced to most archipelagos in the world from polar to tropical islands (Atkinson 1985). Their adverse impacts on biodiversity through direct consumption (Jones, Tershy, Zavaleta, Croll, & Keitt 2008) or synergic indirect effects (Russell 2011) have been well documented and have been proven to be very persistent (Bourgeois, Ouni, Pascal, Dromzée, & Fourcy 2013). Their capacity to cause detrimental effects on native fauna and flora is a consequence of their ability to adapt their biology to novel environments.…”
Section: Introductionmentioning
confidence: 99%